Risk and Uncertainty in Telecare: The Case of the Finnish'Elsi' - Jaakola Joni (FINNISH SOC SCIENCE & TECHNOLOGY STUDIES, 2025)
In recent decades, technologically mediated 'telecare' solutions have become popular for making the care of ageing populations more efficient, productive and targeted in times of economic austerity and care deficits. While telecare has been implemented in care work, caring has increasingly become a practice of managing risks. This paper draws on ethnographic research on the telecare solution 'Elsi' in a Finnish care home setting and examines telecare as a form of risk management. The 'Elsi' telecare system is based on information gathered from floor sensors and alarms caused by different events, such as falls. The argument is that telecare practices deal in many ways with 'uncertainty work' that produces uncertain knowledge, uncertain entities and uncertain values. Furthermore, these uncertainties produce additional work, which creates more duties for the care worker.